2013
DOI: 10.1002/ejoc.201300047
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6H‐Isoindolo[2,1‐a]indol‐6‐ones Through Wittig Reaction and Tandem Reductive Cyclization–Lactamization

Abstract: A convenient and efficient two‐step route to 6H‐Isoindolo[2,1‐a]indol‐6‐ones has been developed starting from o‐nitrobenzaldehydes. The methodology involves Wittig reaction followed by tandem reductive cyclization–lactamization. A series of isoindoloindolones incorporating different substituents on the indole nucleus has been prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[3][4][5][6][7][8][9] For example, a two-step strategy starting from o-nitrobenzaldehydes through wittig reaction and tandem reductive cyclization-lactamization was established by Tilve et al (Scheme 2, route 1). 4 The synthesis of 2a can also be carried out via an intramolecular wittig reaction from ophthalimidobenzyl bromide (Scheme 2, route 2). 5 Griffiths et al reported a convenient route to 2a from 2-(N-phthaloyl)benzoic acid via β-ketophosphonates (Scheme 2, route 3).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] For example, a two-step strategy starting from o-nitrobenzaldehydes through wittig reaction and tandem reductive cyclization-lactamization was established by Tilve et al (Scheme 2, route 1). 4 The synthesis of 2a can also be carried out via an intramolecular wittig reaction from ophthalimidobenzyl bromide (Scheme 2, route 2). 5 Griffiths et al reported a convenient route to 2a from 2-(N-phthaloyl)benzoic acid via β-ketophosphonates (Scheme 2, route 3).…”
Section: Introductionmentioning
confidence: 99%